Perbedaan Estimasi Volume Perdarahan Antara Metode Tes Hemoglobin Dengan Metode Visual Estimasi Pada Ibu Postpartum - Ardi Panggayuh; Jupriyono Jupriyono (Akademi Keperawatan Dharma Husada Kediri, 2017)
Error into account bleeding may contribute to an underestimation of the actual postpartum hemorrhage, postpartum hemorrhage late to recognize. This is especially prominent in order to deal with inadequate facilities where deliveries take place at home and the estimated blood loss using equipment that can not be trusted. In the order of these services, blood may be spilled on the floor, bags, and seep into the ground floor. In addition, estimates of maternal postpartum hemorrhage by midwives generally done by visual estimation, although the method is less accurate. In addition, it is often mixed with amniotic fluid and sometimes with urine, making it difficult to visually estimate by less skilled midwife. The purpose of research is to analyze the difference between the volume of bleeding hemoglobin test method with visual estimation. The population is pregnant women who entered the active phase of labor in BPM